2018
DOI: 10.1007/s10530-018-1874-1
|View full text |Cite
|
Sign up to set email alerts
|

Linear and non-linear effects of goldenrod invasions on native pollinator and plant populations

Abstract: The increased introduction of non-native species to habitats is a characteristic of globalisation. The impact of invading species on communities may be either linearly or non-linearly related to the invaders' abundance in a habitat. However, non-linear relationships with a threshold point at which the community can no longer tolerate the invasive species without loss of ecosystem functions remains poorly studied. We selected 31 wet meadow sites that encompassed the entire coverage spectrum of invasive goldenro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…Therefore, the experimental outcomes regarding the species number can be considered to be satisfactory. Other studies have suggested that the species richness of semi-natural grasslands invaded by Solidago decreases linearly with the Solidago cover (Moro n et al, 2019), indicating that further reduction in the invader cover would be beneficial to the plant species richness in our study.…”
Section: Effect Of Experiments On Biodiversitysupporting
confidence: 53%
See 3 more Smart Citations
“…Therefore, the experimental outcomes regarding the species number can be considered to be satisfactory. Other studies have suggested that the species richness of semi-natural grasslands invaded by Solidago decreases linearly with the Solidago cover (Moro n et al, 2019), indicating that further reduction in the invader cover would be beneficial to the plant species richness in our study.…”
Section: Effect Of Experiments On Biodiversitysupporting
confidence: 53%
“…Moreover, they may spread rapidly if mowing is ceased. Therefore, any reduction of the invaders would be beneficial for ensuring plant diversity (Moro n et al, 2019) and high hay quality and quantity (per the results of this study). The trajectory of cover reduction observed as a function of time suggests that further mowing would reduce the Solidago cover even more.…”
Section: Effect Of Experiments On Solidago Reductionmentioning
confidence: 68%
See 2 more Smart Citations
“…The relationships between ecological impacts and the population density of an IAS have often been examined (also known as density-impact curves), with both linear and non-linear relationships proposed (Nava-Camberos et al 2001;Finnoff et al 2005;Laverty et al 2017;Bradley et al 2019;Moroń et al 2019); however, only a few studies have attempted to link this to the damage costs incurred. For a more thorough investigation of the variety of forms of the cost-density function (i.e., the accumulated cost C as a function of density u), we chose to rely on the functional types proposed by Yokomizo (2009), written as:…”
Section: Accumulated Cost As a Function Of Ias Population Density (Cost-density Functions)mentioning
confidence: 99%